Magnetic Resonance (MR) liver fat quantification in patients with obesity: a comparative study with ultrasound, Body Mass Index (BMI) and Alanine Transaminases (ALT) - Abu Hassan, Hasyma; Nathan, Vimala Sevaloga; Zainudin, Mazalin; Ahmad Apandi, Laila Mastura; Hanipah, Zubaidah Nor (Islamic Republic of Iran Medical Council, 2025)
Background: Non-Alcoholic Fatty Liver Disease (NAFLD), strongly linked to obesity and metabolic syndrome, is a leading cause of liver cirrhosis. Early and accurate diagnosis is essential to prevent progression. NAFLD is commonly diagnosed using ultrasound, and obesity is known to limit the quality of ultrasound assessment. This disadvantage may be eliminated with Magnetic Resonance (MR) modality. MR fat quantification is potentially effective in directly determining hepatic steatosis. This study aimed to evaluate if MR is a suitable option to ultrasound with correlation to Body Mass Index (BMI) and Alanine Transaminase (ALT) in patients with obesity. Methods: A prospective cohort pilot study was conducted in Malaysia between January 2020 and July 2021, involving 34 adult obese patients (BMI range: 30–45 kg/m2). All the patients were subjected to ultrasonography, MR, anthropometrics, and serum ALT measurements. MR Fat fraction (MR-PDFF) and spectroscopy using Stimulated-Echo-Acquisition-Mode (MRS-STEAM) and Point-Resolved-Spectroscopy (MRS-PRESS) were used for fat quantification. The results were analysed using Pearson and Spearman correlation tests. Results: The mean values for BMI and ALT are 37.91 and 20.50 respectively. MR showed a significant positive correlation with ultrasound in quantifying liver fat (MRS-STEAM r=0.713, MRS-PRESS r=0.882 and MR-PDFF r=0.961, p<0.05). MRS-PRESS, MR-PDFF and ultrasound indicated a positive correlation with BMI (MRS-PRESS r=0.408, MR-PDFF r=0.385 and ultrasound r=0.477, p<0.05). MRS-STEAM showed no correlation with BMI. All the three MR acquisitions and ultrasound demonstrated positive correlation with ALT level (MRS-STEAM r=0.389, MRS-PRESS r=0.483, MR-PDFF r=0.478 and ultrasound r= 0.487, p<0.05). Conclusion: Magnetic resonance can be potentially used as a safe alternative tool in managing NAFLD in obese patients. A study with larger sample size with adjustments to confounding parameters is required to evaluate the MR as an effective diagnostic tool for NAFLD in obese patients.